Validity of the AM-PAC "6-Clicks" Inpatient Daily Activity and Basic Mobility Short Forms. Issue 3 (1st March 2014) - Jette, Diane U.; Stilphen, Mary; Ranganathan, Vinoth K.; Passek, Sandra D.; Frost, Frederick S.; Jette, Alan M.
Abstract : Background: Standardized assessment of patients' activity limitations in acute care settings can provide valuable information. Existing measures have not been widely implemented. Objectives: The aim of this study was to provide evidence for validity of scores on Activity Measure for Post-Acute Care (AM-PAC) "6-Clicks" measures of basic mobility and daily activity in acute care. Design: A retrospective measurement study was conducted. Methods: The study used a database from one health system containing "6-Clicks" scores from first and last physical therapist and occupational therapist visits for 84, 446 patients. Validity was analyzed by examining differences in "6-Clicks" scores across categories of patient characteristics; the ability of "6-Clicks" scores to predict patients' having more than one therapy visit; correlation of "6-Clicks" scores with Functional Independence Measure (FIM) scores; and internal responsiveness over the episode of care. Internal consistency reliability also was determined. Results: The "6-Clicks" scores differed across patients' age, preadmission living situation, and number of therapy visits. The areas under receiver operating characteristic curves derived using "6-Clicks" scores at the first visit to predict patients receiving more than one visit were 0.703 and 0.652 using basic mobility and daily activity scores, respectively. The "6-Clicks" scores at the final visit were correlated with scores on subscales of the FIM completed on admission to inpatient rehabilitation facilities ( r =.65 and .69). Standardized response means were 1.06 and 0.95 and minimal detectable changes with 90% confidence level (MDC90 ) were 4.72 and 5.49 for basic mobility and daily activity scores, respectively. Internal consistency reliability of basic mobility and daily activity scores was .96 and .91, respectively. Limitations: Using clinical databases for research purposes has limitations, including missing data, misclassifications, and selection bias. Rater reliability is not known. Conclusions: This study provides evidence for the validity of "6-Clicks" scores for assessing patients' activity limitations in acute care settings.